2022
DOI: 10.2166/wst.2022.096
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond conventional wastewater treatment plants within circular bioeconomy concept – a sustainability assessment study

Abstract: Wastewater treatment plants (WWTP) have extensive energy processes that undermine their economic and environmental performance. In this context, the integration of wastewater treatment with other biochemical processes such as co-digestion of sludge with organic wastes, and production of value-added products at their downstream processes will shift conventional WWTPs into biorefinery platforms with better sustainability performance. The sustainability of such a biorefinery platform has been investigated herein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…For the second-generation M-SCP route, methane is sourced from biogas plants, sewage treatment plants, and landfills, thereby avoiding the direct release of these gases into the atmosphere and significantly benefiting the environment. It has been reported that the environmental impact of producing 1 ton of M-SCP, soybean meal, and fishmeal corresponds to −711, 7060, and 3000 kg of CO2, respectively, in terms of climate change (Marami et al, 2022b), showing M-SCP with negative carbon emissions.…”
Section: Environmental Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the second-generation M-SCP route, methane is sourced from biogas plants, sewage treatment plants, and landfills, thereby avoiding the direct release of these gases into the atmosphere and significantly benefiting the environment. It has been reported that the environmental impact of producing 1 ton of M-SCP, soybean meal, and fishmeal corresponds to −711, 7060, and 3000 kg of CO2, respectively, in terms of climate change (Marami et al, 2022b), showing M-SCP with negative carbon emissions.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Renewable energy sources, such as wind power and methane CHP, have been extensively studied in the existing assessments. CHP can achieve heat and electricity savings on the biorefinery platform, and while biogas combustion may produce carbon dioxide and result in methane emissions, it is considered biogenic, renewable, and environmentally superior to nonrenewable sources (Marami et al, 2022b). It has been reported that heat substitution from CHP contributed the most to resource savings, accounting for 65% of the total savings (Marami et al, 2022a).…”
Section: Environmental Implicationsmentioning
confidence: 99%
See 1 more Smart Citation